SIMBOL- SIMBOL MINANGKABAU DALAM KARYA SENI LUKIS - ABDUL RAHMAN, Yasrul Sami, S.Sn., M.Sn., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2017)
This final work aims to visualize the symbols of Minangkabau in painting, with the aim of learning to get to know more about Minangkabau culture that should be deserved to be preserved. The embodiment of the painting displays characters or objects that represent the theme or in accordance with the concept of the author's work. Methods and steps in the process of cultivation work begins with preparation, elaboration, synthesis, concept realization until presented to the public through the exhibition. This final work gives sensitivity to the community of art lovers to Minangkabau culture in the form of values contained depth which is depicted through 10 (ten) titles of painting.Kata Kunci: Simbol-Simbol Minangkabau, Seni Lukis